Effects of Low Level Laser Therapy in Focal Soft Tissue Rheumatism: A Randomized Control Trial - Moonmoon, Taslima Hoq; Moyeenuzzaman, Md; Mohammad Salek, Abul Khair; Shakoor, Md Abdus; Haque, Md Ziaul; Hafez, Fahmida (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Treatment of focal soft tissue rheumatism is very important. Objective: The purpose of the present study was to see the effectiveness of low level laser therapy for the patients suffering from focal soft tissue rheumatism. Methodology: This randomized control trial was carried out in the Department of Physical Medicine and Rehabilitation at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from March 2006 to August 2006 for a period of 6(six) months. The patients having focal soft tissue rheumatism were selected from the dept. of Physical medicine and Rehabilitation who were referred from other outpatient department of BSMMU and also from general practitioners outside the hospital. Patients were divided into two (02) groups designated as study group who were treated with Low level laser therapy, NSAIDs under the coverage of Omeprazole and ADL advice and control group who were treated with NSAIDs under the coverage of Omeprazole and ADL advices. Each group was treated and followed up for six weeks. Result: A total number of 44 patients were recruited for this study who were presented with different focal soft tissue rheumatism. Of these 44 patients, 32(73.0%) patients were female and 12 (27.0%) were male. Maximum patients belong to 31 to 50 years of age group in both sexes. The clinical improvement of group A was 84.0% and group B 60.0%. Results of the two groups were within narrow range. Conclusion: In conclusion though cannot be established, yet LLLT prove to be of some benefit to focal soft tissue rheumatism patients. Journal of National Institute of Neurosciences Bangladesh, 2018;4(1): 18-22